El modelo de gestión “Landlord Port” y su relación con el desarrollo portuario en el Perú - Rodríguez Muente, Eduardo Santiago (2021)
Port development and growth are phenomena that are having more and more impact in the world. They have become very important tools since their logistic capabilities allow the efficient movement of goods of various types (Containers, Bulk, Liquids, etc.). Most producing countries depend on the quality and decentralization of their port services to be able to offer products to the global market; for this reason, the larger and more developed a port is, the more goods it will move efficiently. Peru, on the other hand, is a country that still lacks efficiency in its main ports, which causes economic backwardness. Despite the geographical advantage that Peru has by being in the center of the Pacific coast of South America and even the fact that currently its port management models in are of the "LandLord port" type, according to Hernández Velasquez and Ibarra Santos (2018), these are not being managed in the best way as there is no optimum point between the public and private sector. This research work analyzed in detail the direct and indirect relationships of managing ports with the "LandLord port" model, which involves privatizing infrastructure investment through Peruvian government concessions. A quantitative methodology was employed, in which the data collection technique was used through a structured questionnaire and was applied to a sample, selected by convenience of 20 qualified professionals with experience in the port, logistics and foreign trade fields to obtain reliable information that led to the results, conclusions and final recommendations. In addition, after analyzing the results of the field work, the main critical points of the Peruvian government's management and of the Peruvian private companies that prevent the country's main ports from becoming equal or more competitive than those of Latin America were detected.